Management of Myasthenic Crisis in the Intensive Care Unit - Putra, Angga Permana; Zulfariansyah, Ardi (Journal of Society Medicine, 2025)
Introduction: Myasthenia gravis (MG) is an autoimmune neuromuscular disorder characterized by muscle weakness and fatigability due to impaired neuromuscular transmission. Approximately 15–20% of patients develop myasthenic crisis requiring endotracheal intubation and mechanical ventilation. Management is challenging in the presence of comorbidities, necessitating careful selection of immunomodulatory therapy. Case Description: A 39-year-old woman was admitted to the General Intensive Care Unit of Dr. Hasan Sadikin Hospital with progressive dyspnea and generalized weakness. She was diagnosed with myasthenic crisis complicated by bradyarrhythmia, hypercoagulable state (elevated D-dimer, prolonged PT/INR/APTT), and electrolyte imbalance. Intravenous immunoglobulin (IVIG) was chosen over plasma exchange due to its non-invasive administration, avoidance of large-bore vascular access, more favorable hemodynamic profile, and lower risk of arrhythmia or hypotension. Potential arrhythmogenic effects from fluid shifts and hypotension associated with plasma exchange (reported in ~3% of cases) were considered contraindications in this patient. IVIG was administered at 0.4 g/kg/day for 5 consecutive days. Significant clinical improvement was observed, allowing successful extubation on day 8 and transfer to the High Care Unit on day 9. Conclusion: This case demonstrates the efficacy and safety of IVIG as first-line immunomodulatory therapy in myasthenic crisis with complex comorbidities. A comprehensive multidisciplinary approach combined with appropriate selection of IVIG resulted in rapid clinical recovery and favorable outcome.